2016
DOI: 10.1111/jam.13363
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Aichi virus in molluscan shellfish samples from Galicia (NW Spain)

Abstract: This is the first study that detects the presence of AiV in shellfish from authorized harvesting areas in Spain. Further studies with clinical samples are needed to determine the potential risk of AiV for human health in Galicia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…In the three-year period of the current study, 16 AiV-positive samples were identified, with a prevalence of 5.6%, and specifically, the prevalence trend over the three-year period ranged from a minimum of 2.6% in 2016 to a maximum of 7.8% in 2017 (Table 4). These figures contrast with a 12.0% frequency previously observed for mussels collected in the period of 2014 to 2015 for class A and B areas of the Tyrrhenian Sea [2], but are similar to the 6.0% prevalence observed in Galicia, Spain [37]. For this study, it appears that AiV contamination was influenced by weather conditions, since 2016 was the driest year of the three-year study and 2017 had the most rainfall.…”
Section: Discussioncontrasting
confidence: 82%
“…In the three-year period of the current study, 16 AiV-positive samples were identified, with a prevalence of 5.6%, and specifically, the prevalence trend over the three-year period ranged from a minimum of 2.6% in 2016 to a maximum of 7.8% in 2017 (Table 4). These figures contrast with a 12.0% frequency previously observed for mussels collected in the period of 2014 to 2015 for class A and B areas of the Tyrrhenian Sea [2], but are similar to the 6.0% prevalence observed in Galicia, Spain [37]. For this study, it appears that AiV contamination was influenced by weather conditions, since 2016 was the driest year of the three-year study and 2017 had the most rainfall.…”
Section: Discussioncontrasting
confidence: 82%
“…In France, other study detected AiV in oysters that were linked to a gastroenteritis outbreak and the AiV sequences obtained where similar to those from stool samples analyzed in parallel (Le Guyader et al 2008). More recently, AiV has been detected from shellfish in Spain and Italy (Fusco et al 2017;Rivadulla et al 2017;Terio et al 2018), with prevalence ranging from 1.7 to 12%.…”
Section: Aiv In Shellfishmentioning
confidence: 84%
“…Viral recovery from shellfish homogenates (2 g) samples was carried out following the ISO 15216-1:2017 specifications, with slight modifications as previously described [28,29]. Briefly, known amounts of Mengovirus clone vMC0 were spiked into each sample homogenate (10 µL, 10 3 plaque forming units [PFU]) as a control for the RNA extraction efficiency [30].…”
Section: Methodsmentioning
confidence: 99%
“…Quantification was also carried out following the principles outlined in the ISO 15216-1:2017 as previously described [28,29]. Briefly, standard curves were constructed using serial dilutions of HEV RNA purified from a clinical sample (kindly donated by Dr. A. Aguilera from the University Hospital of Santiago de Compostela, Spain), in which the number of genome copies was plotted against the Ct values.…”
Section: Methodsmentioning
confidence: 99%